2020
DOI: 10.1111/bjh.16460
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive and common features of moderate aplastic anaemia

Abstract: Summary The therapy algorithm for severe aplastic anaemia (sAA) is established but moderate AA (mAA), which likely reflects a more diverse pathogenic mechanism, often represents a treatment/management conundrum. A cohort of AA patients (n = 325) was queried for those with non‐severe disease using stringent criteria including bone marrow hypocellularity and chronic persistence of moderately depressed blood counts. As a result, we have identified and analyzed pathological and clinical features in 85 mAA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(62 reference statements)
1
9
0
Order By: Relevance
“…The differences between patients with severe and nonsevere AA in genomic features were recently reported by Patel J et al [4]. Although at least one mutation was identified in 19% of patients with AA at the time of diagnosis, independently of the severity of the AA, these mutations included DNMT3A, PIGA, SRSF2 and CEBPA and there were no differences in the average number of mutations.…”
Section: Somatic Mutationsmentioning
confidence: 50%
See 2 more Smart Citations
“…The differences between patients with severe and nonsevere AA in genomic features were recently reported by Patel J et al [4]. Although at least one mutation was identified in 19% of patients with AA at the time of diagnosis, independently of the severity of the AA, these mutations included DNMT3A, PIGA, SRSF2 and CEBPA and there were no differences in the average number of mutations.…”
Section: Somatic Mutationsmentioning
confidence: 50%
“…Although at least one mutation was identified in 19% of patients with AA at the time of diagnosis, independently of the severity of the AA, these mutations included DNMT3A, PIGA, SRSF2 and CEBPA and there were no differences in the average number of mutations. Patients with AA had a higher mutation rate/more pronounced mutational burden in comparison to moderate AA (56% vs 19%) which corresponds to the unstable hematopoietic clones and higher risk of evolution [4].…”
Section: Somatic Mutationsmentioning
confidence: 97%
See 1 more Smart Citation
“…This might be partly explained by the different pathogenesis of SAA and NSAA. In a recent study, 31 NSAA was concluded to contain a mix of patients with diverse etiologies which is different from the autoimmune pathogenesis in SAA. They also found the distinctive gene mutation burden between NSAA and SAA which might reflected the different gene background and gave this another explanation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other somatic mutations such as DNMT3A and ASXL1 are associated with worse outcomes. Recently, a study into mutation status and the differences between severe and non-severe AA by Patel et al [47] detected at least one mutation in 19% of patients with AA at the time of diagnosis, independent of the severity of the AA. However, patients with severe AA had a higher mutation rate compared to moderate AA (56% vs. 19%), which corresponds to the unstable hematopoietic clones and higher risk of clonal evolution [47].…”
Section: Impact Of Somatic Mutations On Outcomesmentioning
confidence: 99%